2014
DOI: 10.1111/plb.12184
|View full text |Cite
|
Sign up to set email alerts
|

Relative in vitro growth rates of duckweeds (Lemnaceae) – the most rapidly growing higher plants

Abstract: Relative growth rates (RGR), doubling times (DT) and relative weekly yields (RY) of 39 clones (ecotypes) from 13 species representing all five genera of duckweeds were determined under standardised cultivation conditions. RGR ranged overall from 0.153 to 0.519 day(-1) , DT from 1.34 to 4.54 days and RY from 2.9 to 37.8 week(-1) . The RGR and RY data can be compared directly to other published findings to only a limited extent on account of missing clonal designations for and limited accessibility to previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
231
4
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(298 citation statements)
references
References 38 publications
16
231
4
7
Order By: Relevance
“…The previously published RGRs of 8 additional clones belonging to three of the Wolffia species (Ziegler et al 2015) were integrated in the present data in order to make the data set more comprehensive. Thus, in the present paper growth rates of 33 clones of different Wolffia species investigated under identical, standardized growth conditions were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previously published RGRs of 8 additional clones belonging to three of the Wolffia species (Ziegler et al 2015) were integrated in the present data in order to make the data set more comprehensive. Thus, in the present paper growth rates of 33 clones of different Wolffia species investigated under identical, standardized growth conditions were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, clonal offsprings with identical genetic properties are produced. In a previous paper, we investigated rates of vegetative growth of 13 species of duckweeds belonging to all five genera, i.e., Spirodela, Landoltia, Lemna, Wolffiella, and Wolffia (Ziegler et al 2015). It was shown that the variation in vegetative growth rates exists at the level of clones rather than at the level of species or genera.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Lemnaceae comprises one of the fastest growing angiosperms (Sree et al, 2015c;Ziegler et al, 2015). In some Asian countries, duckweeds have been used for human nutrition for generations (Bhanthumnavin and McGarry, 1971;cf.…”
Section: Introductionmentioning
confidence: 99%